ANALISIS KINERJA KEUANGAN BANK UMUM SYARIAH DARI PERSPEKTIF TATA KELOLA PERUSAHAAN - Carmidah Carmidah; Sukirno Sukirno (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Governance in Islamic banking is not limited to achieving profit or maximizing wealth but is related to stakeholder theory which is considered to align bank performance objectives with the environment and public interest. The purpose of this study was to analyze the effect of corporate governance as proxied by the number of boards of directors, number of sharia supervisory boards, characteristics of the board of directors and number of board meetings on financial performance as proxied by Return On Equity (ROE). The results showed that the number of boards of directors and the characteristics of the boards of directors had a positive influence on Return On Equity in Islamic Commercial Banks in Indonesia.